Study on Women in Medieval Pre-South Indian Art: Exploring the representation and significance of women in Medieval Pre-South Indian Art (Journal of Advances and Scholarly Researches in Allied Education, 2021)
In Indian art, along with the various religious aspects of life, the temporal aspects have alsobeen shaped in a wide dimension. The collective experience and thoughts of the Indian society have beenexpressed in various mediums of art in architecture, sculpture and painting. . In Asian art, various forms ofdivine figures of fairies, gandhas and apsaras, represented by Brahmanical, Buddhist and Jain religions,have been formed.